IMPROVING ELEMENTARY STUDENTS' CRITICAL READING SKILLS THROUGH THE ARCS MODEL APPROACH IN BASIC PROCESS SKILLS - Yulia Rizki Ramadhani; Yenni Rozimela; Atmazaki; Jamaris Jamna; Sufyarma Marsidin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper describes the effectiveness of the ARCS model approach in improving the critical reading skills of elementary students at the basic process skills level. The research used a pre-experimental design method of one group pretest-posttest type with the research subjects of sixth-grade students at SD Negeri 107397 Cinta Damai in Deli Serdang. Data on students' critical reading skills were collected using a previously validated critical reading test instrument. The research results indicate that applying the ARCS model approach in learning critical reading can improve elementary students’ critical reading skills at the basic process skills level. There is a significant improvement in students' skills to analyze, evaluate, and synthesize the information they read and it provides a basis for developing more effective learning approaches. The implications include the integration of the ARCS model in curriculum design and teacher training as well as further research with larger sample populations and broader contexts. It is expected that the application of the ARCS model can enrich teaching at the primary level and advance students' critical thinking skills.